The relation between adverse childhood experiences and moral injury in the Canadian Armed Forces. Issue 1 (31st December 2019) - Battaglia, Anthony M.; Protopopescu, Alina; Boyd, Jenna E.; Lloyd, Chantelle; Jetly, Rakesh; O'Connor, Charlene; Hood, Heather K.; Nazarov, Anthony; Rhind, Shawn G.; Lanius, Ruth A.; McKinnon, Margaret C.
ABSTRACT: Background : There is increasing evidence that moral injuries (MIs) may affect the mental health of Canadian Armed Forces (CAF) members and veterans. Despite knowledge suggesting that MIs are related to multiple negative mental health outcomes, including the onset of post-traumatic stress disorder (PTSD), it is unknown whether pre-traumatic variables, including the presence of childhood abuse, are related to MIs. Objective : This study seeks to investigate the potential relationship between adverse childhood experiences and later onset MI in military members. Methods : Thirty-three patients newly admitted to an inpatient unit for treatment of trauma-related disorders received a standardized self-assessment package, including the PTSD Checklist for DSM-5 (PCL-5), the Moral Injury Events Scale (MIES; adapted for the Canadian context), and the Adverse Childhood Experiences Questionnaire (ACE-Q), which is a retrospective measure of childhood abuse. Results : Analyses revealed a significant relation between childhood emotional abuse and the presence of MI in adulthood. Specifically, emotional abuse during childhood was correlated with total score on the MIES ( p = 0.006) and with its two subscales, perceived betrayals ( p = 0.022) and perceived transgressions ( p = 0.016). These correlations remained significant when controlling for age and gender. Conclusions : Among CAF members and veterans, childhood events are related to the presence of MI during adulthood. These preliminary data are provocative in suggesting that emotional abuse during childhood may increase the likelihood of endorsing MI during adult military service. Further work is needed to identify pre-traumatic variables that may serve to increase risk or enhance resilience to the development of MI in military members. HIGHLIGHTS: Prior research suggests that adverse childhood experiences influence the development of adult post-traumatic stress disorder (PTSD) in civilian and military populations. Moreover, research suggests a relation between PTSD and moral injury (MI) in military populations. The current study finds that experiencing childhood emotional abuse is related to the presence of MI during adult military service, even after controlling for age and gender.